A Potent HDAC Inhibitor, 1-Alaninechlamydocin, from a Tolypocladium sp. Induces G2/M Cell Cycle Arrest and Apoptosis in MIA PaCa-2 Cells - Du, Lin (American Chemical Society and American Society of Pharmacognosy, 2014)
[Image: see text] The cyclic tetrapeptide 1-alaninechlamydocin was purified from a Great Lakes-derived fungal isolate identified as a Tolypocladium sp. Although the planar structure was previously described, a detailed analysis of its spectroscopic data and biological activity are reported here for the first time. Its absolute configuration was determined using a combination of spectroscopic ((1)H–(1)H ROESY, ECD, and X-ray diffraction) and chemical (Marfey’s analysis) methods. 1-Alaninechlamydocin showed potent antiproliferative/cytotoxic activities in a human pancreatic cancer cell line (MIA PaCa-2) at low-nanomolar concentrations (GI(50) 5.3 nM, TGI 8.8 nM, LC(50) 22 nM). Further analysis revealed that 1-alaninechlamydocin induced G2/M cell cycle arrest and apoptosis. Similar to other cyclic epoxytetrapeptides, the inhibitory effects of 1-alaninechlamydocin are proposed to be produced primarily via inhibition of histone deacetylase (HDAC) activity.